2021
DOI: 10.1186/s12916-021-02147-6
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation events in people with chronic kidney disease as a component of multimorbidity: parallel cohort studies in research and routine care settings

Abstract: Background Chronic kidney disease (CKD) typically co-exists with multimorbidity (presence of 2 or more long-term conditions: LTCs). The associations between CKD, multimorbidity and hospitalisation rates are not known. The aim of this study was to examine hospitalisation rates in people with multimorbidity with and without CKD. Amongst people with CKD, the aim was to identify risk factors for hospitalisation. Methods Two cohorts were studied in para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…Strengths of UK Biobank include its size, detailed baseline assessment and measurements including biological samples, follow-up assessments for certain issues, and the availability of long-term linkage to outcome data. This has allowed investigators to explore various aspects of multimorbidity including demographic patterns [ 4 ], prevalence of disease clusters [ 8 ], association with related states such as frailty or sarcopenia [ 9 , 10 ], the impact of lifestyle factors in the context of multimorbidity [ 11 ], and associations between multimorbidity and adverse health outcomes [ 4 , 12 15 ]. Many such analyses would not have been possible using routine data alone, and the sample size of UK Biobank provides considerable statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of UK Biobank include its size, detailed baseline assessment and measurements including biological samples, follow-up assessments for certain issues, and the availability of long-term linkage to outcome data. This has allowed investigators to explore various aspects of multimorbidity including demographic patterns [ 4 ], prevalence of disease clusters [ 8 ], association with related states such as frailty or sarcopenia [ 9 , 10 ], the impact of lifestyle factors in the context of multimorbidity [ 11 ], and associations between multimorbidity and adverse health outcomes [ 4 , 12 15 ]. Many such analyses would not have been possible using routine data alone, and the sample size of UK Biobank provides considerable statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently studied endpoints were related to hospital care utilization. Studies looking at the outcomes of all-cause readmissions and emergency hospitalizations concluded that multimorbidity combinations including CKD consistently showed higher rates of hospital admissions across several European cohorts included in these studies 34,40 . Similar findings were observed in studies exploring potentially avoidable hospitalizations and healthcare costs as outcomes.…”
Section: Ckd Multimorbidity and Health Outcomesmentioning
confidence: 96%
“…We identified ten studies that looked at the association between multimorbidity (including CKD) and negative health outcomes (Table 2) 22,23,[33][34][35][36][37][38][39][40] . The studies were conducted among multimorbid populations in Europe (k = 7), USA (k = 1) and Asia (k = 1).…”
Section: Ckd Multimorbidity and Health Outcomesmentioning
confidence: 99%
“…In one of these studies it was shown that GFR <60 ml/min/1.73 m 2 resulted in a decrease in survival from 25 to 16.4 months compared with patients with GFR ≥60 ml/min/1.73 m 2.13 On the other hand, when CKD is present in a patient, it normally coexists with a median of five other long-term comorbidities, leading to an increased risk of hospitalization of 2-3 times. 14 In turn, in patients with chronic liver disease (CLD), liver-related mortality is the leading cause of death, linked to a 1-year mortality of 1%-3.4% in early stages of cirrhosis and 20-50% in advanced stages. 15 Therefore, coexistence of cancer and CLD is a major therapeutic challenge, especially when chronic treatment with potentially hepatotoxic drugs is needed.…”
Section: Historical Perspectivementioning
confidence: 99%
“…In one of these studies it was shown that GFR <60 ml/min/1.73 m 2 resulted in a decrease in survival from 25 to 16.4 months compared with patients with GFR ≥60 ml/min/1.73 m 2. 13 On the other hand, when CKD is present in a patient, it normally coexists with a median of five other long‐term comorbidities, leading to an increased risk of hospitalization of 2–3 times 14 …”
Section: Historical Perspectivementioning
confidence: 99%